2015
DOI: 10.4103/0970-2113.168137
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of noninvasive ventilation for chronic obstructive pulmonary disease-related respiratory failure in Indian hospitals without ICU facilities

Abstract: Introduction:The majority of Indian hospitals do not provide intensive care unit (ICU) care or ward-based noninvasive positive pressure ventilation (NIV). Because no mechanical ventilation or NIV is available in these hospitals, the majority of patients suffering from respiratory failure die.Objective:To perform a cost-effective analysis of two strategies (ward-based NIV with concurrent standard treatment vs standard treatment alone) in chronic obstructive pulmonary disease (COPD) respiratory failure patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The proper use of NIV in hospitalized and home patients, through appropriate management and monitoring by the staff, allows reducing the costs and time of hospitalization and may prevent disease exacerbations [20][21][22].…”
Section: Importance and Influence Of Staff Training On The Outcome Wimentioning
confidence: 99%
“…The proper use of NIV in hospitalized and home patients, through appropriate management and monitoring by the staff, allows reducing the costs and time of hospitalization and may prevent disease exacerbations [20][21][22].…”
Section: Importance and Influence Of Staff Training On The Outcome Wimentioning
confidence: 99%
“…The authors of the YONIV trial report that the cost-savings were predominantly due to reduced utilisation of intensive care units. The cost benefits of ward-based NIV, versus admission to intensive care, are particularly important for low- and middle-income countries with limited access to critical care facilities [34]. Yeung et al [35] recently published a timely systematic review and Bayesian meta-analysis of randomised controlled trials that evaluated the use of NIV, compared to invasive ventilation, as a weaning strategy in adults mechanically ventilated for at least 24 h. The authors evaluated 25 studies comprising 1609 patients and found that NIV weaning was associated with a lower mortality rate at hospital discharge, shorter duration of invasive ventilation, lower rate of ventilator associated pneumonia, and a shorter length of stay in the intensive care unit.…”
Section: Ward-based Niv As An Alternative To Critical Care Admissionmentioning
confidence: 99%
“…A review of patients presenting to over 100 hospitals in India found equivalent medical therapy and mortality between men and women. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%